Self monitoring of blood glucose in type 2 diabetes: longitudinal qualitative study of patients' perspectives. Issue 7618 (30th August 2007) - Peel, Elizabeth; Douglas, Margaret; Lawton, Julia
Abstract : Objective To explore views of patients with type 2 diabetes about self monitoring of blood glucose over time. Design Longitudinal, qualitative study. Setting Primary and secondary care settings across Lothian, Scotland. Participants 18 patients with type 2 diabetes. Main outcome measures Results from repeat in-depth interviews with patients over four years after clinical diagnosis. Results Analysis revealed three main themes—the role of health professionals, interpreting readings and managing high values, and the ongoing role of blood glucose self monitoring. Self monitoring decreased over time, and health professionals' behaviour seemed crucial in this: participants interpreted doctors' focus on levels of haemoglobin A1c, and lack of perceived interest in meter readings, as indicating that self monitoring was not worth continuing. Some participants saw readings as a proxy measure of good and bad behaviour—with women especially, chastising themselves when readings were high. Some participants continued to find readings difficult to interpret, with uncertainty about how to respond to high readings. Reassurance and habit were key reasons for continuing. There was little indication that participants were using self monitoring to effect and maintain behaviour change. Conclusions Clinical uncertainty about the efficacy and role of blood glucose self monitoring in patients with type 2 diabetes is mirrored in patients' own accounts. Patients tended not to act on their self monitoring results, in part because of a lack of education about the appropriate response to readings. Health professionals should be explicit about whether and when such patients should self monitor and how they should interpret and act upon the results, especially high readings.